Walking speed reduction rates at intersections while wayfinding indoors: An experimental study. (7th April 2020) - Bae, Young‐Hoon; Kim, Young‐Chan; Oh, Ryun‐Seok; Son, Jong‐Yeong; Hong, Won‐Hwa; Choi, Jun‐Ho
Summary: Although there are numerous studies that explain how pedestrians behave, there remains a lack of experimental data on the various factors that can induce walking speed changes. It is important to continue experiments into this topic because, given that pedestrians receive information and select paths during indoor wayfinding in complicated buildings, their walking speed necessarily decreases. Furthermore, the majority of existing studies do not simultaneously explain changes in indoor wayfinding characteristics and in walking speed. To bridge this gap, we present results from an experimental study to indicate the effect that wayfinding at intersections within a building has on human walking speed. We analyzed changes in walking speed by intersection type and path selection direction (by conducting a maze experiment with 77 participants) to arrive at the following results: (a) Human walking speed decreases at intersections; (b) The change in walking speed depends on the type of the intersection and the path selection direction; (c) A multiple regression analysis can be used to model reduction in walking speed by intersection type and path selection direction. This study suggests that evacuation modeling should consider that wayfinding occurs when pedestrians select paths at intersections, which affects their walking speed.